DNA Terminal Breathing Regulated by Metal Ions for Colloidal Logic Gates. Issue 33 (19th July 2013) - Kanayama, Naoki; Takarada, Tohru; Fujita, Masahiro; Maeda, Mizuo
<x xml:space="preserve">Abstract</x> Just keep breathing: A basic set of colloidal Boolean logic gates (AND, OR, and NOT) was constructed on the basis of metal‐regulated terminal breathing of double‐stranded DNA tethered to gold nanoparticle surfaces (see illustration).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>